The impact of green reporting on the emerging stock market around green policy announcements: evidence from Vietnam - Nguyen Thi Hoa Hong; Nguyen Ngoc Hai; Kieu Yen Ngoc; Vuong Minh Ngoc; Nguyen Thi Yen Phuong; Dinh Le Quynh Thu (Sustainable Futures)
This paper investigates the impact of green reporting on the Vietnamese stock market around green policy announcements during 2019–2022 by collecting data from 612 listed companies on the Vietnamese stock exchange. To measure green reporting, the paper employs the Scoring method to evaluate companies’ reports based on five components including water, energy, emissions, waste, and compliance. Utilizing the Event study method and Ordinary Least Squares Regression, our empirical results reveal a positive correlation between green reporting and stock returns, accompanied by a reduction in stock risks. In addition, among the five components of green reporting, emission emerges as the most influential factor affecting the performance of the Vietnamese stock market. Therefore, our findings offer some valuable implications for both listed companies and regulatory authorities seeking to amplify the beneficial effects of green reporting on the Vietnamese stock market.